Penetration and preferential binding of charged nanoparticles to mixed lipid monolayers: interplay of lipid packing and charge density. Issue 7 (11th January 2021) - Chaudhury, Anurag; Debnath, Koushik; Bu, Wei; Jana, Nikhil R.; Basu, Jaydeep Kumar
Abstract : Designing of nanoparticles (NPs) for biomedical applications or mitigating their cytotoxic effects requires microscopic understanding of their interactions with cell membranes. Abstract : Designing of nanoparticles (NPs) for biomedical applications or mitigating their cytotoxic effects requires microscopic understanding of their interactions with cell membranes. Such insight is best obtained by studying model biomembranes which, however, need to replicate actual cell membranes, especially their compositional heterogeneity and charge. In this work we have investigated the role of lipid charge density and packing of phase separated Langmuir monolayers in the penetration and phase specificity of charged quantum dot (QD) binding. Using an ordered and anionic charged lipid in combination with uncharged but variable stiffness lipids we demonstrate how the subtle interplay of zwitterionic lipid packing and anionic lipid charge density can affect cationic nanoparticle penetration and phase specific binding. Under identical subphase pH, the membrane with higher anionic charge density displays higher NP penetration. We also observe coalescence of charged lipid rafts floating amidst a more fluidic zwitterionic lipid matrix due to the phase specificity of QD binding. Our results suggest effective strategies which can be used to design NPs for diverse biomedical applications as well as to devise remedial actions against their harmful cytotoxic effects especially against respiratory diseases.